A survival analysis of South African children under the age of five years - Zeleke Worku (AOSIS, 2011)
The South African Demographic Health Survey data set (SADHS) of 2003 contains massive individual-level information on South African children under the age of five years selected from a random sample of 7756 households. The data set contains data on socio-economic, demographic, health-related and sanitary variables gathered by using multistage cluster sampling. The objective of the study was to identify key predictors of mortality amongst children under the age of five years. Logistic regression analysis and Cox regression were used for data analysis. Under-five mortality was significantly influenced by three predictor variables (breastfeeding, marital status, and ownership of a flush toilet). The hazard ratio of the variable 'breastfeeding' was 3.09 with P = 0.000 and 95% confidence interval (CI) of (1.899, 5.033). The hazard ratio of the variable 'toilet' was 2.35 with P = 0.016 and 95% confidence interval of (1.172, 4.707). The hazard ratio of the variable 'marital status' was 1.74 with P = 0.035 and 95% confidence interval of (1.041, 2.912). Adjustment was factored in for the mother's level of education and wealth index. Opsomming Die Suid-Afrikaanse Demografiese en Gesondheidsopname-datastel (The South African Demographic Health Survey data set [SADHS]) van 2003 bevat 'n enorme hoeveelheid individuele-vlak inligting rakende kinders onder vyf jaar uit 7756 huishoudings in Suid-Afrika. Die datastel bevat inligting rakende sosio-ekonomiese, demografiese, en gesondheidsverwante veranderlikes, en sanitêre-veranderlikes, is versamel deur gebruik te maak van multistadiatrosanalise. Die oogmerk met die studie was die identifisering van sleutelpredikatore ten opsigte van sterftes van kinders onder die ouderdom van vyf jaar. Logistieke-opnameregressie analise en Cox-regressie is gebruik om die data te analiseer. Onder vyf-sterftes word beduidend beïnvloed deur drie predikatorveranderlikes (duurte van borsvoeding, huwelikstatus en toegang tot 'n spoeltoilet). Die risikoverhouding van die borsvoeding-veranderlike was 3.09 met P = 0.000 en 'n 95% sekerheidsinterval van (1.899, 5.033). Die risikoverhouding van die toiletveranderlike was 2.35 met P = 0.006 en 95% sekerheidsinterval van (1.172, 4.707). Die risikoverhouding van die huwelikstatus-veranderlike was 1.74 met P = 0.035 en 95% sekerheidsinterval van (1.041, 2.912). Aanpassings is gemaak vir die opvoedingsvlak van die moeder asook die welgesteldheidsindeks.